Sedum nanlingense (Crassulaceae), a new species from Guangxi, China - Zou, Chun-Yu; Meng, Shi-Yong; Lu, Zhao-Cen; Liu, Yan (Phytotaxa, 2020)
Sedum nanlingense (Crassulaceae), a new species from Guangxi, is described and illustrated here. We analyzed its morphological characteristics, which are largely similar to S. onychopetalum and S. kiangnanense. However, the morphology of this new species differs from other taxa in some important ways, including its 3-merous flowers, which contain six stamens and three carpels. Molecular phylogenetic analysis based on nuclear DNA internal transcribed spacer (ITS) sequences resolved S. nanlingense as a distinct clade, lending further support to its classification. Phylogenetic analysis showed that this new species is closely related to S. onychopetalum and S. kiangnanense.